Oxytocin in Women’s Health and Disease - Liu, Ning; Yang, Haipeng; Han, Liqun; Ma, Mingxing (Frontiers in Endocrinology, 2022)
Oxytocin (OT) is a nonapeptide mainly produced in the supraoptic and paraventricular nuclei. OT in the brain and blood has extensive functions in both mental and physical activities. These functions are mediated by OT receptors (OTRs) that distributed in a broad spectrum of tissues with dramatic sexual dimorphism. In both sexes, OT generally facilitates social cognition and behaviors, facilitates parental behavior and sexual activity and inhibits feeding and pain perception. However, there are significant differences in OT levels and distribution of OTRs in men from women. Thus, many OT functions in men are different from women, particularly in the reproduction. In men, the reproductive functions are relatively simple. In women, the reproductive functions involve menstrual cycle, pregnancy, parturition, lactation, and menopause. These functions make OT regulation of women’s health and disease a unique topic of physiological and pathological studies. In menstruation, pre-ovulatory increase in OT secretion in the hypothalamus and the ovary can promote the secretion of gonadotropin-releasing hormone and facilitate ovulation. During pregnancy, increased OT synthesis and preterm release endow OT system the ability to promote maternal behavior and lactation. In parturition, cervix expansion-elicited pulse OT secretion and uterine OT release accelerate the expelling of fetus and reduce postpartum hemorrhage. During lactation, intermittent pulsatile OT secretion is necessary for the milk-ejection reflex and maternal behavior. Disorders in OT secretion can account for many women-specific diseases. In menopause, the reduction of OT secretion account for many menopausal symptoms and diseases. These issues are reviewed in this work.